2010
DOI: 10.1111/j.1469-8986.2010.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal generator patterns of olfactory event-related brain potentials in schizophrenia

Abstract: To better characterize neurophysiologic processes underlying olfactory dysfunction in schizophrenia, nose–referenced 30–channel electroencephalogram was recorded from 32 patients and 35 healthy adults (18 and 18 male) during detection of hydrogen sulfide (constant-flow olfactometer, 200 ms unirhinal exposure). Event-related potentials (ERPs) were transformed to reference–free current source density (CSD) waveforms and analyzed by unrestricted Varimax–PCA. Participants indicated when they perceived a high (10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 93 publications
6
26
1
Order By: Relevance
“…Further, the study demonstrated that similar results were obtained for CSDs derived from different recording montages and systems. In a replication study using the same task, Kayser et al (2013) investigated clinical high-risk (CHR) subjects at prodromal phase of psychosis and healthy controls and obtained similar olfactory CSD findings for N1 sink and P2 source, and thus closely replicated the previous findings of Kayser et al, (2010c). In addition, the results showed that three patients who later developed psychosis had poorer odor detection and thresholds, along with marked reductions of N1 and P2 (in the absence of significant group differences between CHR and control subjects), suggesting that olfactory measures may be of utility in predicting the transition from prodromal phase to psychosis among CHR subjects.…”
Section: Schizophreniasupporting
confidence: 73%
See 2 more Smart Citations
“…Further, the study demonstrated that similar results were obtained for CSDs derived from different recording montages and systems. In a replication study using the same task, Kayser et al (2013) investigated clinical high-risk (CHR) subjects at prodromal phase of psychosis and healthy controls and obtained similar olfactory CSD findings for N1 sink and P2 source, and thus closely replicated the previous findings of Kayser et al, (2010c). In addition, the results showed that three patients who later developed psychosis had poorer odor detection and thresholds, along with marked reductions of N1 and P2 (in the absence of significant group differences between CHR and control subjects), suggesting that olfactory measures may be of utility in predicting the transition from prodromal phase to psychosis among CHR subjects.…”
Section: Schizophreniasupporting
confidence: 73%
“…Furthermore, methodological improvements for the CSD techniques have been very rare and slow. One obvious exception to this limitation is the work by Kayser, Tenke and Colleagues, who have innovated some methods, for example, to extract PCA components of the CSD (Kayser and Tenke, 2003; Tenke and Kayser, 2005) and successfully implemented this approach to study clinical domains (Kayser et al, 2006, 2009, 2010a,b,c, 2012, 2013, 2014; Tenke et al, 2008, 2010, 2011). Other concerns of CSD are related to its methodological limitations, which may be addressed by future studies: 1) the transformation of the EEG potentials into the CSD leads to a partial data loss, since the low-spatial-frequency (LSF) components are attenuated (Hjorth, 1980; cf.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous neuroimaging studies of OI have not found any specific contribution of the piriform cortex to OI (Kareken et al 2003;Savic et al 2000;Suzuki et al 2001). Still, some studies using olfactory event-related potentials suggest that cortical processing in the early components of the olfactory cortices is impaired in schizophrenia, Parkinson, and AD (Kayser et al 2010;Morgan and Murphy 2002;Peters et al 2003;WelgeLüssen et al 2009), and that the P2 component may be particularly involved in OI (Turetsky et al 2003). Activation of the posterior piriform cortex has been shown in a number of studies of PS with peak coordinates similar to those in the present study (Gottfried et al 2002;Poellinger et al 2001;Savic et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, there is less tightening of the posterior cricoarytenoid muscle and greater lateral cricoarytenoid muscle action to further narrow the vocal cord slit by 10-40% [15,[18][19][20]. The process may entail development of a perpetual hyperexcitable state as laryngeal-controlled neuronal networks react inappropriately to sensory messages from subcortical and other regions of the brain [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%